Business ethics concepts & cases - Velasquez, Manuel G. (Pearson Prentice Hall, 2006)
CD-ROM contains: ABC news segments: Enron's fall -- Unocal in Burma -- AIDS in Africa -- Mircosoft antitrust trial -- To drill or not to drill -- Ford/Firestone debacle -- Ralphs -- Gap's labor problems.